Translation the basics - House, Juliane (The basics, 2024)
"Translation: The Basics is an accessible and comprehensive introduction to the study of translation. This revised edition includes two new chapters on culturally embedded concepts and translation in global business. Combining traditional text-based views with the context of translation in its widest sense, it presents an integrated approach to methodology in order to critically address influences such as power and gender, as well as cultural, ethical, political and ideological issues. Key theoretical issues are explained with reference to a range of case studies, suggestions for further reading and a detailed glossary of terms, making this the essential guide for anyone studying translation and translation studies"--Provided by publisher.